Serious infections under treatment with TNF-alpha antagonists compared to traditional DMARDs in patients with rheumatoid arthritis - DİRESKENELİ, RAFİ HANER (SPRINGER HEIDELBERG, 2006)
Biological treatments aiming to neutralize TNF-alpha (tumour necrosis factor alpha) (infliximab, adalimumab and etanercept) are increasingly used to treat rheumatoid arthritis (RA). Although increased frequency has not been observed in randomized clinical trials with TNF-alpha antagonist agents, postmarketing surveillance suggests that infections might be serious consequences of these therapies. Our aim was to compare infections in patients with RA under treatment with disease-modifying antirheumatic drugs (DMARDs) and TNF-alpha antagonists in a university outpatient rheumatology clinic in Turkey. A total of 130 RA patients treated with DMARDs and 48 treated with TNF-alpha antagonists were analysed for the incidence of infections. Patients taking TNF-alpha antagonists were also reviewed for infections before these therapies. The incidence of serious infections was 7/100 patient-years before TNF-alpha antagonists and 8.6/100 patient-years in DMARDs group. The incidence rose to 17/100 patient-years during therapy with TNF-alpha antagonists. In patients with RA on routine follow-up, treatment with TNF-alpha antagonists seems to carry an increased risk of infections compared to traditional DMARDs.
Keywords: infection; TNF-alpha antagonists; rheumatoid arthritis; TUBERCULOSIS INFECTION; THERAPY